Application of electrochemical biosensing in HIV detection: a progress review - Peixue DENG; Li YE; Rongfeng CHEN; Sanqi AN; Junjun JIANG; Hao LIANG (Editorial Office of Chinese Journal of Public Health, 2023)
Electrochemical biosensors have advantages of miniaturization, low cost, high sensitivity, rapid detection and low detection limit, and have attracted extensive attention in the field of human immunodeficiency virus (HIV) detection. This paper reviews research progress in electrochemical biosensor technology for HIV nucleic acid or antigen detection, compares it with routine detection methods, and analyzes the advantages and disadvantages of electrochemical biosensor detection.